2003
DOI: 10.2133/dmpk.18.1
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Absorption of Drugs Mediated by Drug Transporters: Mechanisms and Regulation

Abstract: The absorption of drugs from the gastrointestinal tract is one of the important determinants for oral bioavailability. Development of in vitro experimental techniques such as isolated membrane vesicles and cell culture systems has allowed us to elucidate the transport mechanisms of various drugs across the plasma membrane. Recent introduction of molecular biological techniques resulted in the successful identification of drug transporters responsible for the intestinal absorption of a wide variety of drugs. Ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 112 publications
(111 reference statements)
1
44
0
2
Order By: Relevance
“…As regards membrane transport in the small intestine, several transporters have been suggested to contribute to drug absorption Katsura and Inui, 2003;Daniel, 2004;Sai and Tsuji, 2004), and in particular, P-gp is involved in regulation of the intestinal permeation of various xenobiotics (Terao et al, 1996). Midazolam shows high membrane permeability and is categorized as BCS class I (Wu and Benet, 2005).…”
mentioning
confidence: 99%
“…As regards membrane transport in the small intestine, several transporters have been suggested to contribute to drug absorption Katsura and Inui, 2003;Daniel, 2004;Sai and Tsuji, 2004), and in particular, P-gp is involved in regulation of the intestinal permeation of various xenobiotics (Terao et al, 1996). Midazolam shows high membrane permeability and is categorized as BCS class I (Wu and Benet, 2005).…”
mentioning
confidence: 99%
“…20) It has also been suggested that diphenhydramine and procainamide share a common organic cation transporter. 7) As shown in Fig. 3, the finding that thiamine, but not diphenhydramine, exerted a significant trans-stimulatory effect on bacampicillin uptake in Caco-2 cells suggests that bacampicillin and thiamine share a common transport system on the Caco-2 cell membranes.…”
Section: Discussionmentioning
confidence: 67%
“…It is well known that a variety of organic cations are absorbed via specialized transport systems in the small intestine. 7,8) It is therefore possible that a kind of organic cation transporter is unexpectedly involved in the intestinal absorption of bacampicillin. Caco-2 cells express a large number of transporters with which to handle various endogenous and exogenous organic cations such as azasetron, 9) carnitine, 10,11) choline, 12) diphenhydramine, 13) guanidine, 14) 1-methyl-4-phenyl-pyridinium, 15) nicotine, 16) and thiamine.…”
mentioning
confidence: 99%
“…Thus, oral bioavailability is one of the key considerations for discovery and development of a new chemical entity (NCE). It is well recognized that poor oral bioavailability is one of the major causes of therapeutic variability, associated with the variable drug exposure (Beierle et al 1999;Bardelmeijer et al 2000;Katsura and Inui 2003). This is particularly important for drugs with narrow therapeutic window or potential for resistance development such as antibiotics and cytotoxic drugs (Bardelmeijer et al 2000).…”
Section: Introductionmentioning
confidence: 99%